A Thorough Comparative Analysis of PI and Sliding Mode Controllers in Permanent Magnet Synchronous Motor Drive Based on Optimization Algorithms - Fatemeh Khorsand; Reza Shahnazi; Esmael Fallah (AUT Journal of Electrical Engineering)
In this paper, the speed tracking for permanent magnet synchronous motor (PMSM) in field oriented control (FOC) method is investigated using linear proportional-integral (PI) controller, sliding mode controller (SMC) and its advanced counterparts. The advanced SMCs considered in this paper are fuzzy SMC (FSMC) and sliding mode controller with time-varying switching gain (SMC+TG) which can effectively cope with chattering, an inherent harmful phenomenon in SMC. Regardless of all the works done to replace PI controller with SMC and its advanced counterparts, a thorough comparison of the PMSM drive behavior under mentioned controllers is still missing. This paper attempts to fill in this gap, by providing a fair and in-depth comparison of the PMSM drive operation by using PI and sliding mode speed controllers. In this paper, in order to design and provide a fair framework for comparison the performance and robustness of these four controllers a suitable cost function is defined to manage the performance effectively. Thus, based on this cost function a nonlinear optimization problem is defined. To solve the optimization problem and consequently derive the optimal values for the parameters of the controllers, particle swarm optimization (PSO) and grey wolf optimization (GWO) algorithms are employed. The performance and robustness of the PMSM drive using four optimal controllers are studied in the presence of different conditions and uncertainties. Numerical results demonstrate that SMC and its advanced counterparts cannot offer the superior behavior for all conditions and their superiority is less than it is often stated in the literature.